Building Information Modelling Uptake: Tool Training in Nigeria - Hamma-adama, Mansur; Kouider, Tahar; Salman, Huda (Open Science Journal, 2018)
Computer Aided Design software and their kind are generally considered as Building Information Modelling (BIM) tools; moreover the sophistication level of one determines its maturity level. Education and research are the background to innovation while training is a window to continuity in skills transfer. The BIM uptake in the developing countries is significantly lagging behind; amongst various reasons is the lack of trained professionals. Experts are evolving from the industry professionals who are first trained in the university. This study determined the capacity of Nigerian universities in providing BIM tools training for BIM adoption in Architecture, Engineering and Construction (AEC). The study is quantitative in nature, with the primary data collected through a structured questionnaire survey within the built environment and engineering schools of Nigerian universities. The collected data were analysed using descriptive statistics. The institutions are physically ready with relatively sufficient hardware, however technically not ready due to insufficiency of up to date software. There is a significant correlation between software availability and proficiency level of training, while no correlation between academic qualification and the training proficiency. More than 70% of the students are graduating on ‘file based collaboration’ – 2D and 3D CAD knowledge with proficiency level between limited and practical application. However, the collaborative software training received proficiency level of basic to practical application; a 13% trained on collaboration software is very little to providing experts for the industry. This reveals a clear setback in the tools training to carter for the BIM uptake in the country.